2020
DOI: 10.1111/jce.14647
|View full text |Cite
|
Sign up to set email alerts
|

A novel local impedance algorithm to guide effective pulmonary vein isolation in atrial fibrillation patients: Preliminary experience across different ablation sites from the CHARISMA pilot study

Abstract: Introduction Recently, a novel technology able to measure local impedance (LI) and tissue characteristics has been made available for clinical use. This analysis explores the relationships among LI and generator impedance (GI) parameters in atrial fibrillation (AF) patients. Characterization of LI among different ablation spots and procedural success were also evaluated. Methods and Results Consecutive patients undergoing AF ablation from the CHARISMA registry at five Italian centers were included. A novel rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 20 publications
3
45
1
Order By: Relevance
“…Segreti et al reported that the LI drop after an RF application was higher than the GI drop and that the LI drop was an effective indicator of a successful lesion formation. Although the major findings were similar, the degree of the LI drop (14.8 Ω) and GI drop (3.7 Ω) differed from those of the present study 13 . The differences in the patient background such as the BMI and contact between the catheter tip and myocardium might have been the reason for this difference.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Segreti et al reported that the LI drop after an RF application was higher than the GI drop and that the LI drop was an effective indicator of a successful lesion formation. Although the major findings were similar, the degree of the LI drop (14.8 Ω) and GI drop (3.7 Ω) differed from those of the present study 13 . The differences in the patient background such as the BMI and contact between the catheter tip and myocardium might have been the reason for this difference.…”
Section: Discussioncontrasting
confidence: 72%
“…LI is able to distinguish the degree of catheter–tissue contact, because healthy myocardium displays a larger resistivity compared with blood pool. The past studies reported that this catheter provided a high electrogram spatial resolution, which may aid in identifying critical isthmuses and gaps on a line of block, and that the LI drop measurements during RF applications give an indication of the tissue contact and subsequent effective lesions 11‐14 . However, the data on this novel catheter during the initial AF ablation procedure, such as a PV isolation and single ring box isolation, have scarcely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These include systems designed to assess the real‐time effectiveness of ablation, 9 such as DirectSense, a novel technology that measures local impedance (LI) through mini‐electrodes on the tip of a dedicated ablation catheter (IntellaNAV Mifi OI, Boston Scientific). The use of highly localized impedance measurements to provide insight into tissue characteristics and their real‐time evaluation seem to be helpful to precisely assess the electrical contact of the catheter and tip stability 10,11 . However, although preliminary data on acute success and ablation endpoints have been encouraging, clinical evidence on the long‐term outcome in a large population of AF patients is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It also helps to distinguish catheter-tissue contact from non-contact [10] and might be an adjunct to fluoroscopy, local electrograms and 3D maps in assessing tissue contact in lowvoltage areas. [7] The cases presented are examples of how DirectSense TM capabilities are useful not only in assessing effective lesion formation, but also in directing RF applications to proper sites. The first case showed that information derived from LI was more helpful than ablation signals in confirming the presence of the gap and in guiding the ablation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…This system uses highly localized impedance measurements to provide insight into tissue characteristics, and may provide more useful information regarding catheter stability and lesion formation than the use of generator impedance alone. [7] Here, we describe how localized impedance information can be leveraged in order to guide the successful ablation of complex arrhythmias.…”
Section: Introductionmentioning
confidence: 99%